Analisis Status Mutu Air di Danau Toba Menggunakan Metode STORET: Studi Kasus Keramba Jaring Apung di Desa Tongging - Hidayati, Hidayati; Zulfa Hanie, Meidina; Heickel Kenza Ginting, Kevin; Fadhila, Fadhila; Ashari Syawal, Ferdy (Fakultas Teknik UMRI, 2025)
Lake Toba as the largest volcanic lake in Southeast Asia faces a serious threat in the form of water pollution due to the activities of Floating Net Cages (KJA). This study aims to evaluate the status of water quality in the waters of Lake Toba, especially in Tongging Village, Karo Regency. The evaluation was carried out using the STORET method approach. Water samples were taken at three different time conditions (before, during, and after feeding) at five strategic points representing KJA, around KJA, and river inlets. The results showed that the concentrations of phosphate and nitrate had exceeded the quality standards of PP No. 22 of 2021, reaching 0.072 mg/L and 9.950 mg/L, respectively. The highest STORET method score was -35, indicating severely polluted water conditions. These findings emphasize the need for sustainable fisheries management in Lake Toba.